Impact of Environmental, Social, and Governance Scores on Market Reaction: Evidence of Top 80 Companies Listed from Idx80 - Darmasaputra, Alan; Widyadhana, Mosses Aryadhewa; Sany, Sany; Tjondro, Elisa (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
This paper will discuss the impact of the individual Environmental, Social, and Governance scores on market reaction. This study will specifically focus on the IDX80 index, which lists companies that are not only profitable but also have good ESG scores. The panel data for the study will be taken from 2019 to 2023, and the Dynamic Panel Model will be used to see how the scores over the year influenced the market price. The final sample consists of 31 companies with 155 firm-years for the observation. The findings show that the Environmental scores have a significant positive impact on market reactions, but are not significantly impacted by Social and Governance scores. The study suggests an early stage of ESG adoption in Indonesia and the positive trend growth will be beneficial for companies to promote ESG activities. The implication for managers is to incorporate ESG activities as they positively impact the market reaction, particularly activities related to Environmental issues. The limitation of this study is that the data for the individual scores for the Environmental, Social, and Governance are limited making the sample size small. A further limitation is that the data analyzed during and post-COVID-19 time might suggest a different result comparably.